Faktor-Faktor yang Mempengaruhi Minat Petani Terhadap Budidaya Kelapa Berkelanjutan di Kecamatan Batang Anai Kabupaten Padang Pariaman - Afifah, Fathiya; Elviati, Elviati; Khairad, Fastabiqul (Mahesa Research Institute, 2026)
This study aims to identify the factors that influence farmer’s interest in sustainable coconut cultivation in Batang Anai District, Padang Pariaman Regency. The study sample consisted of 60 respondents who met the criteria of having at least 20 coconut trees and trees that were more than 25 years old. The method used was a survey with multiple linear regression analysis. The results showed that the variables of land area, price, harvest time, and maintenance influenced farmer’s interest by 63.3%, while other factors outside the scope of this study influenced the remaining 36.7%. The price factor had a negative influence, meaning that price changes could either decrease or increase farmers' interest. The results of this study are expected to serve as a reference for local governments in developing strategic programs to improve selling prices and marketing efficiency, thereby ensuring the sustainability of coconut cultivation.